1970
DOI: 10.1002/jsfa.2740210810
|View full text |Cite
|
Sign up to set email alerts
|

Studies on a kerosene‐like taint in mullet (Mugil cephalus)I.—general nature of the taint

Abstract: A taint resembling kerosene is sometimes present in mullet (Mugil cephalus) caught near Brisbane, Australia. It is not thought to be the same as the ‘petroleum’ taint sometimes found in cod and salmon which is caused by the thermal decomposition of dimethyl‐β‐propiothetin to dimethyl sulphide. The ‘kerosene’ taint is removed from the body tissue of mullet by solvent extraction and is associated with the hydrocarbon fraction of the extract. Tainted fish differ from untainted fish in that they have fatinfiltrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1970
1970
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Polycyclic aromatic hydrocarbons (PAH) are a large and diverse group of chemicals having two or more aromatic rings and are a major component of petroleum hydrocarbons. These PAHs have been detected in commercial seafoods (Dunn and Fee, 1979;Howgate et al, 1977;Uthe et al, 1984;Williams et al, 1985) and are capable of causing taint or off-flavors in shellfish and finfish (Mackie et al, 1972;Scarratt, 1980;Vale et al, 1970). PAHs are of special concern due to the carcin-ogenic@ of a number of members of this class of compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAH) are a large and diverse group of chemicals having two or more aromatic rings and are a major component of petroleum hydrocarbons. These PAHs have been detected in commercial seafoods (Dunn and Fee, 1979;Howgate et al, 1977;Uthe et al, 1984;Williams et al, 1985) and are capable of causing taint or off-flavors in shellfish and finfish (Mackie et al, 1972;Scarratt, 1980;Vale et al, 1970). PAHs are of special concern due to the carcin-ogenic@ of a number of members of this class of compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Aromatic hydrocarbons, particularly the alkylbenzenes containing nine to ten carbons, are commonly responsible for OF (Motohiro 1983). Vale et al (1970) and Shipton et al (1970) reported on a "kerosene" taint in mullet taken from the Moreton Bay area and the Brisbane River in Queensland, Australia. This taint appeared in the mullet at the start of winter when they began their migration from the southern estuaries to the warmer waters to the north.…”
Section: Tainting Of Aquatic Animals By Contaminated Watermentioning
confidence: 99%
“…Oil spills have also resulted in off-flavors in aquatic species with Shipton et al (1970) and Vale et al (1970) describing a 'kerosene' taint in mullet taken from the Moreton Bay area of the Brisbane River in Australia. The off-flavors were associated with fish caught around docks or industrial sewage outlets.…”
Section: Off-flavors From the Environmentmentioning
confidence: 99%